The value of the antibiotic B2 supplement Terramycin Bi-Con TM-10 vitamin B2 premix (Fortafeed 2-49-C), and Aureomycin B12 supplement Aurofac 2A in the protein supplement for fattening spring pigs in the dry-lot in summer. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
In 1956-57 experiments with swine were designed to secure information on the maximum use of alfalfa meal in protein supplemental mixtures as a dry-lot substitute for pasture, since pastures for swine in Kansas are often poor, inadequate, or unavailable. The pigs in these tests received, with their grain, mixed protein supplements which contained varying quantities of alfalfa meal. The mixed protein supplement that gave best results for the two years tested was one of 4 parts tankage, 4 parts soybean meal, and 3 parts alfalfa meal.
Keywords: Swine; Terramycin; Aureomycin; Protein